Status Kadar Hemoglobin Dan Jenis Leukosit Pada Pasien TB Paru Di Surabaya - Ellies Tunjung Sari Maulidiyanti (Universitas Muhammadiyah Surabaya, 2020)
Abstract Tuberculosis (TB) is a global public health problem, the World Health Organization (WHO) stated when it occurred around 7-8 million TB cases with 1.3-1.6 million deaths each year (WHO, 2012). TB is a specific multi-systemic infection, which can cause diverse clinical manifestations in each organ system, so, the clinical presentation of this disease is also quite diverse. Hematologic findings in TB are not uncommon and usually occur due to non-immunological factors. Hematological disorders in the form of anemia, leukocytosis, neutrophilia, lymphopenia, lymphocytosis and increased blood slope rate (LED), thrombocytosis and thrombocytopenia. On blood tests, when TB starts to become active there is a slight leukocytosis with a slightly abnormal type of count. Anemia is reported in 16-94% of patients with pulmonary TB. One's anemia status can be assessed one of them through examination of hemoglobin. The purpose of this study was to analyze the levels of hemoglobin and types of leukocytes in pulmonary TB patients in Surabaya. This examination uses an automatic analyzer with the working principle of SLS (sodium lauryl sulfate). Samples of the blood of pulmonary TB patients in several hospitals in Surabaya .. From 30 samples obtained an average hemoglobin level of 11.5 gr / dl, as many as 10 (33.4%) samples whose levels were within normal limits and 20 (66.6%) sample levels were below normal values. Examination of leukocyte count showed that there were 8 samples (26.6%) of normal neutrophil cells, 22 samples (73.4%) abnormal, 5 lymphocytes of normal cells (16.6%), 25 samples (83% abnormal), abnormal 25 samples (83%) , 4%), normal monocyte cells were 17 samples (56.6%) and abnormal were 13 samples (43.4%). Keywords: haemoglobine, leukosit type, TB patients